HBV and HCV test uptake and correlates among men who have sex with men in China: a nationwide cross-sectional online survey. (19th May 2018) - Fitzpatrick, Thomas; Pan, Stephen W; Tang, Weiming; Guo, Wilson; Tucker, Joseph D
Abstract : Objectives: Hepatitis B virus (HBV) and hepatitis C virus (HCV) cause substantial morbidity and mortality in low-income and middle-income countries, including China. WHO guidelines recommend men who have sex with men (MSM) receive HBV and HCV screening. The purpose of this study was to determine the proportion of MSM in China who have HBV and HCV tested and identify correlates of test uptake. Methods: We conducted an online cross-sectional survey of young MSM in China. Respondents were asked to report previous HBV and HCV testing, sociodemographic information, sexual risk factors for hepatitis infection, other STI testing and primary care physician (PCP) status. Associations were analysed by logistic regression. Results: 503 eligible MSM completed the survey. 41.0% (206/503) of MSM had HCV tested, and 38.2% (60/157) of MSM with no or uncertain HBV vaccination had HBV tested. In multivariate analysis, HCV testing was correlated with HBV testing (adjusted OR (aOR) 22.98, 95% CI 12.11 to 43.60), HIV testing (aOR 3.64, 95% CI 1.92 to 6.91), HIV-positive status (aOR 1.78, 95% CI 1.07 to 2.98) and having a PCP (aOR 2.40, 95% CI 1.44 to 3.98). Among MSM with no or uncertain HBV vaccination, HBV testing was correlated with HCV testing (aOR 80.85, 95% CI 20.80 to 314.33), HIV testing (aOR 5.26, 95% CI 1.81 to 15.28), HIV-positive status (aOR 3.00, 95% CI 1.22 to 7.37) and having a PCP (aOR 2.69, 95% CI 1.00 to 7.26). Conclusions: Our data suggest many young MSM in China have not received hepatitis testing. HCV testing rates were lower than those recently reported among MSM in Australia and the USA. The strong correlation between HBV and HCV testing suggests bundled testing interventions may be useful for MSM in China. Men with a PCP were more likely to have received hepatitis testing, consistent with literature demonstrating the importance of primary care in expanding access to testing.